(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Some 36 Naemi ewes , 4 rams were typed for blood potassium and hemoglobin , and 19 offspring were typed for blood potassium . HK (High potassium) gene frequencies for ewes, rams and lambs were of the order of 0.87, 0.87 and 0.89 respectively , for the HbB gene the frequency for sheep was 0.97 . HK sheep had a significantly higher in birth weight and body weight (p<0.01), and HK sheep showed better fiber diameter than that in LK (low potassium) sheep, (p<0.05), and there was no significant differences in regarding of fiber length. The association between HbB (Hemoglobin type B) and HK type and fitness were proposed as the explanation of the high gene frequency of this type.